Categorical improvements in disease severity in patients with major depressive disorder treated with vilazodone: post hoc analysis of four randomized, placebo-controlled trials - Durgam S (Dove Medical Press, 2016)
Suresh Durgam,1 Changzheng Chen,1 Carl P Gommoll,1 John Edwards,1 Leslie Citrome2 1Allergan, Jersey City, NJ, USA; 2Department of Psychiatry and Behavioral Sciences, New York Medical College, Valhalla, NY, USA Background: In three 8-week studies of vilazodone 40 mg/d (NCT00285376, NCT00683592, and NCT01473394) and a 10-week study of vilazodone 20 or 40 mg/d (NCT01473381), adults with major depressive disorder (MDD) showed significantly greater improvement with vilazodone versus placebo in global disease severity as measured by mean change from baseline in Clinical Global Impression of Severity (CGI-S) score. To assess the proportion of patients achieving clinically meaningful improvement, a post hoc pooled analysis was conducted using categorical shifts in disease severity based on CGI-S scores at baseline and end of treatment (EOT). Methods: Analyses were conducted in the pooled intent-to-treat population (N=2,218). Definitions of categorical shifts included CGI-S ≥4 (moderately ill or worse) at baseline to CGI-S ≤2 (normal or borderline ill) at EOT; CGI-S ≥5 (markedly ill or worse) at baseline to CGI-S ≤2 at EOT; and CGI-S ≥6 (severely ill or worse) at baseline to CGI-S ≤3 (mildly ill or better) at EOT. Results: At baseline, 2,217 patients were moderately ill or worse. The percentage who improved to normal or borderline ill was significantly higher with vilazodone than with placebo (40.0% versus 27.8%; odds ratio [OR] =1.7, P<0.001; number needed to treat [NNT] =9). In the 979 patients who were markedly ill or worse at baseline, the percentage who improved to normal or borderline ill was significantly higher with vilazodone than with placebo (36.8% versus 25.5%; OR =1.7, P<0.001; NNT =9). The small number of severely ill patients at baseline (n =43) provided inadequate power to detect statistically significant between-group differences, but an NNT =5 was found for improvement to mildly ill or better. Conclusion: Categorical shift analyses, defined using baseline and EOT CGI-S scores, showed that significantly higher proportions of patients had clinically meaningful improvements in global disease severity with vilazodone 20–40 mg/d versus placebo. This type of analysis may be useful for evaluating the effects of antidepressant treatment in adults with MDD. Keywords: depression, antidepressant, global improvement, clinical trial